PENGEMBANGAN MULTIMEDIA INTERAKTIF PEMBELAJARAN TEKNIK MENGGAMBAR FASHION POSE - Januar Dwirani; Suciati Suciati (Fesyen Perspektif, 2015)
Fashion pose drawing technique learning are based on the field studies results in basic design mode in Education University of Indonesia specialy  Program Study Fashion Design of Education subjects and still conventional with the use of power point and a white board as the media. For those students requires interactive learning (two-way or more communication from the components of communication, where students as the user can control the multimedia itself). The use of fashion pose drawing technique learning as the multimedia can help learners to learn optimally both in their own learning as well as in the classroom, and can help educators to make learning more innovative. Fashion pose drawing technique begins with the theory of fashion pose drawing, and then fashion pose drawing technique. The production of this multimedia aims to develop one existing learning media into the new media in the form of interactive multimedia that are adjusted to the needs of learners. The stages of this interactive multimedia production are with creating multimedia design, multimedia development, verification and validation, and analysis of verification results. The appropriate method for this study is the approach of RD (Research and Development) method. The results of the validation by matter experts get 74.99% eligibility average percentage value,  by multimedia experts get 87.59% eligibility average percentage value and by the user get 96.87% eligibility average percentage value, so it can be elaborated that the eligibility standards in interactive multimedia of fashion pose drawing technique learning are included in the very good category.